Are cardiac patients in Saudi Arabia provided adequate instructions when they should not drive? - Rami M Abazid (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Objective: Driving capability can be significantly affected by different heath disorders; cardiovascular diseases (CVDs) should be considered when assessing patients for medical fitness to drive (MFTD). The aim of this study was to evaluate the awareness of Saudi patients about driving recommendations and to assess the incidence of motor vehicle accidents (MVAs) among cardiac patients. Materials and Methods: We conducted a cross-sectional survey-based study. Male patients diagnosed with CVDs and who were visiting outpatient departments were invited to complete a questionnaire regarding their awareness of driving recommendations. Patients’ demographics, clinical diagnosis, echocardiography parameters, and time-to-CVD diagnosis were all obtained from the patients’ medical records. Women were excluded because it was illegal for women to drive in Saudi Arabia during the study period. Results: In total, 800 men were included, with a mean age of 54 ± 12 years. Driving counseling had been provided to 241 participants (30%). Of these, 207 (25%) were advised not to drive for a period of between one week and six months. Five percent of the patients had a history of MVAs during the follow-up period of 6.2 ± 4 years. We found that the presence of a dyspnea ≥2, according to the New York Heart Association (NYHA), and a history of loss of consciousness (syncope/pre-syncope) were significantly associated with accidents (46% vs. 20%, P < 0.0001 and 41% vs. 10%, P < 0.0001, respectively). Conclusion: Patient–physician discussion about MFTD was only performed with 30% of the patients with CVDs in Saudi Arabia. Dyspnea NYHA class ≥2 or a prior history of syncope were significantly associated with the incidence of MVAs.